Mineralization of Soft Tissues in Panoramic Radiographies - Aguilar DDS, MSc, José; Domínguez DDS, MSc, Andrés; Guaman, Gabriela; Medina-Sotomayor DDS, MSc, PhD, Priscilla (Odovtos - International Journal of Dental Sciences, 2019)
Introduction: The prevalence of pathological conditions that appear as radiopacities at the level of the soft tissues in panoramic radiographs is a problem that occurs worldwide in the population, being this radiographic finding the initial diagnosis of other systemic affections. Objectives: the aim of this research was to identify the frequency of mineralized radiopacities that are found at the soft tissue level in panoramic radiographs. Material and methods: it was analyzed 347 radiographs of patients over 20 years of age, treated in the “Clínica Docente Odontológica” of the Universidad Católica de Cuenca, Sede Azogues, Ecuador from December 2017 to may 2018. Results: a prevalence of 0% of tonsillolith and atheroma was found, 1% of calcified lymph nodes and of electrolytes, 2% of sialolith, 4% of unilateral stylohyoid ligament calcification, 23% of calcification of bilateral stylohyoid ligament and 65% did not present calcifications of the soft tissues. Conclusion: it was possible to identify that the most frequent radiopacity at soft tissue level is the calcified bilateral stylohyoid process.